1998
DOI: 10.1007/bf01451053
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage lesions of the knee following immobilisation or destabilisation for 6 or 12 weeks in rabbits

Abstract: Eighty mature female New Zealand White rabbits were sacrificed 6 or 12 weeks after either section of the medial collateral and the anterior cruciate ligaments with removal of the anterior third of the medial meniscus of one knee, or immobilisation of one knee, using the contralateral non-treated knee as the control. The area of degenerated joint surface of the distal femur, and water and proteoglycan content were measured, and the articular cartilage stained using haematoxylin and eosin and safranin O. Destabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Joint motion has been accepted as an essential adjunctive component in the biological restoration of articular cartilage after injury [16][17][18][19][20][21][22] , whereas joint immobilization can be deleterious to joint function 20,[22][23][24] . Distraction alone, particularly with the use of external fixation, carries the potential for the development of arthrofibrosis, which can be deleterious to joint reconstruction 25,26 .…”
mentioning
confidence: 99%
“…Joint motion has been accepted as an essential adjunctive component in the biological restoration of articular cartilage after injury [16][17][18][19][20][21][22] , whereas joint immobilization can be deleterious to joint function 20,[22][23][24] . Distraction alone, particularly with the use of external fixation, carries the potential for the development of arthrofibrosis, which can be deleterious to joint reconstruction 25,26 .…”
mentioning
confidence: 99%
“…The deleterious effects of immobilization on cartilage have been demonstrated in numerous studies (Hong 1996, Jortikka et al 1997, Fu et al 1998, Vanwanseele et al 2002. The resulting changes are similar to those seen in osteoarthritis.…”
Section: The Role Of Cartilage In Arthrodesismentioning
confidence: 73%
“…Partial joint immobilisation damages cartilage and causes chondrolysis, cloning of chondrocytes and invasion of the tide mark in rats, rabbits and dogs (Kahanovitz et al 1984, Smith et al 1992, Kim et al 1995, Shevtsov et al 1995, Hong and Henderson 1996, Jortikka et al 1997, Fu et al 1998. Compression of the knee joint in rabbits results in chondrolysis and erosion of the cartilage (Gritzka et al 1973).…”
Section: The Normal Jointmentioning
confidence: 99%
“…We recently showed that 6 weeks of immobilisation produce moderate degenerative joint disease in the rabbit knee [3], with fairly extensive degenerated joint surface areas. Water content significantly increased after 6 weeks of immobilisation, and proteoglycan content decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Although unavoidable in some instances, immobilisation can cause long-lasting damage to the articular cartilage [2], evident at both histological and biochemical analysis [3]. Early motion following musculoskeletal injuries is advocated [4], and recent work has shown that 3 months of immobilisation in dogs produces prolonged proteoglycan alterations, although collagen organisation remains largely unchanged [2].…”
Section: Introductionmentioning
confidence: 99%